Root-associated bacteria modulate the specialised metabolome of Lithospermum officinale L. - Alicia Varela Alonso; Alicia Varela Alonso; Henry D. Naranjo; Angélique Rat; Nebojša Rodić; Nebojša Rodić; Christina I. Nannou; Christina I. Nannou; Dimitra A. Lambropoulou; Dimitra A. Lambropoulou; Andreana N. Assimopoulou; Andreana N. Assimopoulou; et al. (Frontiers in Plant Science, 2022)
Bacteria influence plant growth and development and therefore are attractive resources for applications in agriculture. However, little is known about the impact of these microorganisms on secondary metabolite (SM) production by medicinal plants. Here we assessed, for the first time, the effects of bacteria on the modulation of SM production in the medicinal plant Lithospermum officinale (Boraginaceae family) with a focus on the naphthoquinones alkannin/shikonin and their derivatives (A/Sd). The study was conducted in an in vitro cultivation system developed for that purpose, as well as in a greenhouse. Targeted and non-targeted metabolomics were performed, and expression of the gene PGT encoding for a key enzyme in the A/S biosynthesis pathway was evaluated with qPCR. Three strains, Chitinophaga sp. R-73072, Xanthomonas sp. R-73098 and Pseudomonas sp. R-71838 induced a significant increase of A/Sd in L. officinale in both systems, demonstrating the strength of our approach for screening A/Sd-inducing bacteria. The bacterial treatments altered other plant metabolites derived from the shikimate pathway as well. Our results demonstrate that bacteria influence the biosynthesis of A/Sd and interact with different metabolic pathways. This work highlights the potential of bacteria to increase the production of SM in medicinal plants and reveals new patterns in the metabolome regulation of L. officinale.